Análise in vitro da precisão de técnicas de esplintagem na moldagem de implantes no esquema all-on-four - Pimentel, Gustavo Henrique Diniz [UNESP] (2014)
Passively fitting superstructures are a prerequisite for long-lasting osseointegration of dental implants. Accurate transfer of the implant positions from the mouth to a definitive stone cast is a crucial step for ensuring the adaptation of components. Among the various techniques proposed, there is no consensus on which one is the most effective. The aim of this study was to evaluate in vitro the accuracy of different splinting methods in the impression of implants under standardized laboratory conditions. To obtain the master model, an aluminum metal matrix was developed, presenting four perforations, parallel (simulating conventional prosthesis and angled (simulating All-on-four system). Analogs were fixed and, on them, metal structures were fabricated. For straight implants, the groups were divided into GSUR: non-splinted square transfers; GUR-R: transfers splinted acrylic resin; GUM R: transfers splinted with metal rod, cyanoacrylate and acrylic resin. For angled implants, the same techniques were compared: GSU-A, GUR-A, GUM-A. The impression was performed with polyvinyl siloxane impression material and a standardized tray to control variables. The models were cast in standardized matrix with type IV plaster stone. For the measurements, a software (Leica QWin) received the images from a video camera coupled to a Leica stereomicroscope. The KruskalWallis test, associated with Dunn's test, with significance level of 5%, was applied. For straight implants, statistically significant difference between groups (KruskalWallis test; p <0.001) was observed. The difference was between GUR-R (186.71 µm) and master model (110.40 µm) and between GUR-R and the other groups (GSU-R: 108.27 µm and GUM-R: 92.98 µm). For angled implants, no statistically significant difference (p = 0.492) was found between the groups (MM-A: 68.52 µm; GSU-A: 60.80 µm; GUR-A: 56.54 µm; GUM-A: 69.33 µm. ..(Complete abstract electronic access below)